Coaching transitions across borders: the pursuit of individuals advancing coaching careers in the competitive global landscape of Olympic sports - Kim, Y. J.; Tak, M. (International Sport Coaching Journal, 2025)
Intensified international competition for sporting success has facilitated coaches` cross-national migration, which constitutes a space for coaches` career transitions and development. This paper examines elite coaches` international migration as part of coaching career transitions within the context of the global sporting arms race. Using a qualitative case study design, data were generated from documents and semistructured interviews with six South Korean coaches who had moved to Western nations to coach national teams in two Olympic sports. The analysis reveals an underlying mechanism of the coaches` international mobility: dual imbalances existing between the sending and receiving countries—one in the levels of sporting performance; and the other in the perceived levels of modernisation in coaching cultures and sports systems. The migration opportunities were created by the performance imbalance between the home nation and destinations amid the structural context of the global sporting arms race. However, equally important is the individuals` strategic initiative to seize the opportunities for their career development and mitigate the perceived modernisation imbalance in coaching practices. By highlighting coaches` agentic capacity to navigate their career pathways within the global context, this study contributes to the literature on both international coach migration and coaching transitions.